Peranan Usability Dalam Meningkatkan Citra Merek Melalui Kepuasan Pelanggan, Dan Kepercayaan Pada Website Online Travel Agent - Setiawan, Edhie Budi; Utami, Nabilah Puteri; Kholdun, Amrulloh Ibnu; Pratiwi, Sekar Widyastuti; Novianto, Didin Dwi (Gorontalo Management Research, 2025)
The use of digital technology by the public has increased, including for online Travel Agent Websites. This study aims to determine the role of Usability in increasing Customer Satisfaction, Trust, and Brand Image on the Pegipegi Online Travel Agent Website. The method used in this study is quantitative descriptive. The types of data used are primary and secondary data, where primary data is obtained from questionnaires while secondary data is obtained from journals and books. In this study, sampling was carried out using the purposive sampling method of 171 respondents. The analysis method in this study uses the Structural Equation Model - Partial Least Square (SEM-PLS). The results of this study state that customer satisfaction has a positive effect on trust and brand image, and trust has a positive effect on brand image. While usability has a significant impact on customer satisfaction and trust, it does not have a significant effect on brand image. Indirectly, usability affects brand image through satisfaction and trust. This shows that usability can improve a brand image if consumers are satisfied and trust the online travel agent's website.